Efficient biosensing through 1D silver nanostructured devices using plasmonic effect. (11th July 2018) - Afsheen, Sumera; Munir, Musarat; Isa Khan, Muhammad; Iqbal, Tahir; Abrar, Muhammad; Tahir, Muhammad Bilal; Rehman, Jalil-Ur; Riaz, Khalid Nadeem; Ijaz, Mohsin; Nabi, Ghulam
Abstract: The current work explores the excitation of surface plasmon polaritons (SPPs) on a one dimensional (1D) silver nano-grating device, simulated on glass substrate, which can sense a very small change in the refractive index of an analyte adjacent to it. The most recent modeling technique finite element analysis is applied in this work by using a COMSOL RF module. The models of 1D grating devices of different slit widths with fixed periodicity and film thickness are simulated. The data is collected and then used to study higher refractive index unit per nanometer (RIU/nm) as well as the effect of the widths of the slits on the RIU. A number of investigations are done by the simulated data, like a dip in the transmission spectra of p-polarized light. This dip is due to SPP resonance with the variation of slit width. Furthermore, the most fascinating part of the research is the COMSOL modeling that provides an opportunity to look into factors affecting higher RIU/nm, while visualizing the cross-sectional view of the grating device and strong electric field enhancement at the surface of the metallic device. When the slit width is almost equal to half of the periodicity of the grating device, SPP resonance increases and it is at maximum for the slit width equal to two-thirds of the periodicity, because the coupling efficiency is at maximum.